ORIENTATION DEPENDENT DIFFERENCES IN ENERGY BREAKDOWN FOR SINGLE OFFICES IN BELGRADE CONTINENTAL CLIMATE - Grujić, Marija; Knežević, Anđela; Knežević, Nikola (Journal of Applied Engineering Science, 2024)
Energy breakdown information is an important factor in the process of building design. It gives the designer direction in the decision-making process of choosing the most adequate building design. Location parameters, thus the climate conditions, are the first determining factor for energy breakdown in buildings – it is determining whether we are dealing with a heating or cooling dominated climate. But in the real environment, there are further parameters that can influence energy breakdown in office buildings, such as site parameters. Site characteristics determine the available orientation of the building’s facade and define obstructions to incoming solar radiation. This study deals with differences in orientation dependent energy breakdown in office buildings for Belgrade continental climate. The influence of site obstructions on incoming solar radiation was neglected due to the comparative nature of this study. A set of four different highly glazed facades of a single office was combined with a set of four different glazing types, resulting in sixteen models. The simulation was carried out with full and partial control of visual and thermal comfort. The results in this study show that energy breakdown for different orientations of a single office can have great variations. These variations in energy breakdown are primarily connected with the duration and intensity of insolation on the façade and properties of glazing, such as the percentage of glazed area on the façade (window-to-wall parameter (WWR)) and solar factor (g) and visual transmittance (τ) of glazing and the level of integrated systems for comfort control.
Keywords: energy breakdown, glazed facades, single offices, administrative buildings